A multidisciplinary social communication and coping skills group intervention for adults with acquired brain injury (ABI): A pilot feasibility study in an inpatient setting - Appleton, S.; Browne, Allyson; Ciccone, N.; Fong, K.; Hankey, G.; Lund, M.; Miles, A.; Wainstein, C.; Zach, J.; Yee, Y. (2011)
There is evidence that individuals with an acquired brain injury (ABI) are at increased risk of developing psychological problems and that they commonly experience difficulties in social communication, associated with poorer long-term outcomes. Although several relevant group interventions have been evaluated, there has been limited exploration of the feasibility of an ABI inpatient intervention. This nonrandomised pilot study tested the feasibility of an inpatient multidisciplinary social communication and coping skills group intervention within 1-year post traumatic/ nontraumatic ABI. Seven participants completed a 4-week group program (3 × 1 hour sessions per week) facilitated by a speech pathologist and clinical psychologist and were assessed pre/post intervention and at 3 months with the La Trobe Communication Questionnaire, Correct Information Unit analysis, Hospital Anxiety and Depression Scale, Mini International Neuropsychiatric Interview, Coping Self-Efficacy scale and World Health Organization Quality of Life assessment. Most participants improved between baseline and 3 months post intervention in terms of greater informativeness and efficiency of connected speech and reduced anxiety and they provided positive feedback about the group program. Despite the challenges and limitations of this pilot study, the findings are encouraging and support both the value and feasibility of developing such a program into routine inpatient rehabilitation services.